Exploring Inductive Grammar Teaching: English Teacher Perspectives - Didin Nuruddin Hidayat (IJEE (Indonesian Journal of English Education), 2017)
ABSTRACT In the past few decades, the discussion of what grammatical structures to teach, and how to teach them remains controversial (Ellis, 2006). This research study aimed to explore the role of inductive grammar teaching toward specific grammatical structure, i.e. the second conditional or the unreal/hypothetical conditional. In light of this, ten English teachers were involved in this study, providing beneficial feedback through their experience in English language teaching. They were given two sessions of inductive grammar teaching, and were asked to provide feedback. The results showed that inductive grammmar teaching possessed its strengths and weaknesses. One strength would be from its ability in engaging more active participation from the students. However, a notable weaknessess was in terms of its lack of opportunities in explicit grammatical explanation. ABSTRAK Dalam beberapa dekade terakhir, diskusi tentang struktur tata bahasa apa yang perlu diajarkan, dan bagaimana mengajarkan struktur tata bahasa tersebut tetap menjadi isu yang kontroversial (Ellis, 2006). Penelitian ini bertujuan untuk mengeksplorasi peran pengajaran tata bahasa induktif terhadap struktur tata bahasa tertentu, yaitu the second conditional atau the unreal/hypothetical conditional. Untuk itu, sepuluh guru bahasa Inggris dilibatkan dalam penelitian ini, memberikan umpan balik yang bermanfaat melalui pengalaman mereka dalam bidang pengajaran bahasa Inggris. Mereka diberi dua sesi pengajaran tata bahasa induktif, dan diminta untuk memberikan umpan balik. Hasilnya menunjukkan bahwa pengajaran grammmar induktif memiliki kekuatan dan kelemahannya. Salah satu kekuatan berasal dari kemampuannya dalam melibatkan partisipasi yang lebih aktif dari para siswa. Namun, salah satu kelemahan yang menonjol adalah dalam hal kurangnya peluang dalam menjelaskan tata bahasa secara eksplisit.   How to Cite: Hidayat, D.N. (2017). Exploring Inductive Grammar Teaching: English Teacher Perspectives. IJEE (Indonesian Journal of English Education), 4(2), 111-119. doi:10.15408/ijee.v4i2.8538.